The Mediterranean method : your complete plan to harness the power of the healthiest diet on the planet--lose weight, prevent heart disease, and more! - Masley, Steven (Harmony Books, 2019)
From southern Italy, Sardinia, and France to Spain, Greece, and Northern Africa the Mediterranean region is synonymous with sparkling azure waters and clear blue skies. It's also home to most of the world's longest-lived and vibrantly healthy people. Now we know why! Repeatedly ranked the #1 diet by U.S. News and World Report, the Mediterranean eating style--abundant seafood, vegetables, fruits, beans and nuts; lots of olive oil; a wide variety of herbs and spices; and even dark chocolate and red wine--has been scientifically proven to maintain a healthy gut and healthy weight, thereby reducing your risk for heart disease, dementia, memory loss, and many cancers in the process. Taking this famously healthy and life-enhancing "prescription" one step further, Dr. Steven Masley--renowned physician, nutritionist, bestselling author, and trained chef--offers all the flavors and benefits of the Mediterranean diet, but with a "skinny" twist: he focuses on delicious ingredients with a low-glycemic load. Including 50 recipes for food everyone at the table will love--from hearty breakfasts, crowd-pleasing appetizers, soups, and sides, to family-style salads, memorable main meals, and irresistible desserts--The Mediterranean Method is a revolutionary program for losing weight and maintaining the amazing health you regain. Slim down and protect your heart, your brain, and your healthy longevity--all while you enjoy the amazing bounty, variety, and joy of Mediterranean cooking!